2021
DOI: 10.1371/journal.pone.0252835
|View full text |Cite
|
Sign up to set email alerts
|

Association between well-being and compliance with COVID-19 preventive measures by healthcare professionals: A cross-sectional study

Abstract: Importance Knowledge and attitude influence compliance and individuals’ practices. The risk and protective factors associated with high compliance to these preventive measures are critical to enhancing pandemic preparedness. Objective This survey aims to assess differences in mental health, knowledge, attitudes, and practices (KAP) of preventive measures for COVID-19 amongst healthcare professionals (HCP) and non-healthcare professionals. Design Multi-national cross-sectional study was carried out using el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
(40 reference statements)
0
10
0
1
Order By: Relevance
“…In the presence of an infected passenger, physical distancing can help minimize the number of people infected but not prevent infection altogether when passengers do not wear masks. On the other hand, the latest epidemiological research shows that masks are effective in preventing or at least significantly reducing covid-19 virus spread Leung, et al [14,12,15]. There are public transportation systems currently running large occupancies with passenger spacing below the two-meter physical distance rule and no covid-19 outbreaks attributed to public transportation when everyone wears masks, as recently reported for Japan.…”
Section: Empirical Reviewmentioning
confidence: 90%
“…In the presence of an infected passenger, physical distancing can help minimize the number of people infected but not prevent infection altogether when passengers do not wear masks. On the other hand, the latest epidemiological research shows that masks are effective in preventing or at least significantly reducing covid-19 virus spread Leung, et al [14,12,15]. There are public transportation systems currently running large occupancies with passenger spacing below the two-meter physical distance rule and no covid-19 outbreaks attributed to public transportation when everyone wears masks, as recently reported for Japan.…”
Section: Empirical Reviewmentioning
confidence: 90%
“…Correspondingly, better compliance with COVID-19 preventive measures was associated with better well-being. [ 17 ] A study even noted that practice of more preventive behaviors is associated with decreased depressive symptoms among Chinese university students. [ 14 ] Moreover, students who personally know a COVID-19-positive person may perceive themselves as at higher risk of acquiring the disease and thus may report better preventive practice.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 10 12 13 14 ] Some studies targeted the general population[ 6 9 10 ] and health workers. [ 15 16 17 ] Studies among university and college students in the Philippines[ 11 13 ] and other countries such as Libya,[ 12 ] China,[ 18 ] Indonesia,[ 19 ] Japan,[ 20 ] the United Arab Emirates,[ 21 ] and Portugal[ 22 ] were also conducted. Published researches up to July 30, 2020, have also been reviewed in another study.…”
Section: Introductionmentioning
confidence: 99%
“…Housing area also affects adaptation, with men living in rural areas or small towns showing worse adaptation. Yue et al [37], in a study related to knowledge regarding COVID-19, concludes that women and people living in urban areas show more positive indicators.…”
Section: Calamity Experiencementioning
confidence: 99%
“…The level of knowledge and attitudes toward COVID-19 are different among groups with different ages, genders, education levels, marital statuses, and in different regions [37]. In a study by Yue et al [38], it is concluded that higher education level, being female, being married, being a healthcare professional, and living in an urban area had a significant and positive impact on the knowledge about COVID-19.…”
Section: Introductionmentioning
confidence: 99%